Factors that Shape the Competitiveness of Small Innovative Companies Operating in International Markets with a Particular Focus on Business Advice - Edward Stawasz (Journal of Entrepreneurship, Management and Innovation)
The aim of the presented paper is to identify the significance of selected determinants of the competitiveness of small, innovative enterprises operating in international markets that use business advice. The achievement of this goal required identifying the determinants of the competitiveness of small companies (characteristics of managers, characteristics of enterprises) as well as examining the motives, areas and effects of using business advice. The issue of business knowledge absorptive capacity as a determinant of the competitiveness of small enterprises and the effectiveness of using external business knowledge was also presented. The second part of the paper presents the results of empirical research conducted using the CATI technique on a sample of 67 small, innovative Polish enterprises operating in international markets and simultaneously benefiting from business advice. The conducted research confirmed the hypothesis of a significant, moderating influence of business advice on the system of competitiveness determinants of enterprises. The hypothesis concerning a positive relationship between business advice and enterprises’ capacity for absorbing business knowledge, and indirectly their competitiveness, was also confirmed. Improving the competitiveness of enterprises requires using business advice and enhancing their business knowledge absorptive capacity.